Kitan szavak listája Ligeti Lajos MTA-ra hagyott jegyzeteiben: Számnevek - Apatóczky, Ákos Bertalan (Távol-keleti Tanulmányok, 2020)
The late Professor Louis Ligeti was one of the most influential scholars of the 20th century in the fields of Altaic historical linguistics and many others. Ligeti’s personal scholarly notes, according to the provisions of his will, were deposited in the Library of the Hungarian Academy of Sciences (HAS) and were not released for 40 years. In 2018 a special research team of the HAS of Linguistics and Literary Scholarship Section was established to process the contents of the more than 70 large cardboard boxes. This study introduces a segment of his notes on deciphering the Khitan language, dealing with numerals, and offers insights into the current opinion of scholars whenever it varies from Ligeti’s. Minor corrections to the readings of Khitan ‘one’ as well as to the name of the ‘Old(er) Khitan State’ are also suggested.